A Model of an Optimum Currency Area - Luca Antonio Ricci (Kiel Institute for the World Economy (IfW), 2007)
This paper develops a model of the circumstances under which it is beneficial to participate in a currency area. The proposed two-country monetary model of trade with nominal rigidities encompasses the real and monetary arguments suggested by the optimum currency area literature: correlation of real and monetary shocks, international factor mobility, fiscal adjustment, openness, difference in national inflationary biases, and transactions costs. The effect of openness on the net benefits is ambiguous, contrary to the usual argument that more open economies are better candidates for a currency area. Also, prospective member countries do not necessarily agree on whether a given currency union should be created.
Keywords: E52; E42; H77; F36; F33; F31; J61; F02; F4; E61; 330; Optimum currency areas; cost-benefit analysis; exchange rate regimes; currency union; monetary integration